NERACA KARBON PADA SISTEM PERTANIAN BERBASIS PENGGUNAAN ABU SISA DARI BAKARAN DI LAHAN GAMBUT PEDALAMAN (Studi kasus pada Budidaya Tanaman Tomat (Solanum lycopersicum) di Kalampangan) - Surawijaya P; Yovita Yovita (Fakultas Pertanian Universitas Palangka Raya, 2016)
This study aims to: (1) analyzing the balance of carbon in the combustion materials to produce ash burnt on the cultivation of tomato plants (2) analyze the effect of the ash of burn on the physical and chemical properties of peat ombrogen. The results showed that the net balance obtained from this study is negative, this is because the value of the carbon is lost during an emissions in the combustion process wood / roots, weeds urchins and groundcover plants prior to obtaining the ashes of burnt of litter is 0.581 t of carbon/ha is larger than the value of the carbon that is successfully moored by weeds urchins 0.61 t of carbon/ha and litter previous crop (litter plant sweet corn) is 0.437 t of carbon/ ha, only 65, 34% carbon successfully tethered